Fungal networks shape dynamics of bacterial dispersal and community assembly in cheese rind microbiomes - Yuanchen Zhang (Nature Portfolio, 2018)
Interactions with other microbes may inhibit or facilitate the dispersal of bacteria. Here, Zhang et al. use cheese rind microbiomes as a model to show that physical networks created by filamentous fungi can affect the dispersal of motile bacteria and thus shape the diversity of microbial communities.